Strategic Marketing Communication for the N219 Amphibious Aircraft: Aligning Technology and National Policy - Gita Amperiawan; Meyta Saraswaty Putri; Cynthia Sondang Romauli Sipahutar (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The N219 Amphibious Aircraft, developed by PT Dirgantara Indonesia, is positioned as a strategic solution to Indonesia’s persistent challenge of inter-island connectivity, particularly in remote and underdeveloped regions. As part of the national strategic project, the aircraft carries both technical significance and symbolic value in supporting economic development, defense readiness, and national industrial transformation. However, its limited market impact highlights the need for a more integrated and narrative-driven marketing communication strategy. This study analyzes the current communication approach of the manufacturer and proposes enhancements based on four key theoretical perspectives: customer value proposition design, market-driving strategy, purpose-driven branding, and strategic narrative theory. Using a qualitative method that includes stakeholder interviews and narrative analysis, the research reveals that existing communication remains overly technical and fragmented. To address this, a multidimensional communication model is proposed, connecting product-level messaging with broader national policy narratives. The conclusion emphasizes that the N219 must be framed not merely as a transportation product, but as a national policy tool that advances Indonesia’s development goals, technological sovereignty, and global positioning. These insights contribute to the strategic marketing of high-technology products in public sector and defense-oriented industries.